Semiotyczne ograniczenia zakresu modernizacji dawnych przekładów biblijnych - Duda, Henryk (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The most important translations of the Bible into Polish, i.e. the Catholic Jakub Wujek Bible (1599) and the Protestant Gdańsk Bible (1632) were written at the end of the reformation period and were renewed and used in catholic churches and protestant communities until the first half of the 20th century. The reprints were systematically updated. In the 20th century the need to translate again the Holy Scripture into Polish was recognized. There were a few attempts at that in the second half of the previous century. They were always accompanied by heated debates which referred to the need of new translations as well the ways translators adopted to render in Polish selected books, sentences or even words. A religious text functions in a specific system of a higher level, i.e. religion. Religion is understood here as a culture text according to the Tartu-Moscow Semiotic School. Owing to this interpretation, religion has its own language built onto natural language. Text in natural language constitutes only a fragment of a bigger sign entity. To put it most simply, since a natural text is a subcomponent of a semiotic religious text, any change introduced in the former disrupts the coherence of cultural meaning on a higher level. Because of “a secondary modeling system” (a term coined by Yuri M. Lotman) the language of religious texts is always a bit archaic. This very modeling system prevents the propellers of modernization from a more thorough linguistic update of old biblical translations in Poland and, more often than not, does not let translators depart too far from the translation tradition. Translated by Agnieszka Bryła-Cruz